EVALUATION OF CLINICAL BIOCHEMISTRY OF BLOOD IN BITCHES AFFECTED WITH PYOMETRA - GUPTA, A K; DHAMI, A J; PATEL, S B; SHAH, R G (The Indian Journal of Animal Reproduction, 2023)
Nine pyometric and eight healthy bitches were included to evaluate their plasma biochemical, enzymaticand sex steroid profile before and after ovario-hysterectomy. The pre-operative levels of plasma urea nitrogen(PUN), creatinine and total cholesterol were significantly (P
Keywords: Bitch; Pyometra; Clinical Biochemistry; Ovario-hysterectomy